Endometriosis: A Review of Systematic Reviews and Meta-Analysis - YILMAZ, Mehmet (MAS Journal of Applied Sciences, 2022)
Endometriosis is a common disease with typically delayed diagnosis. Its prevalence is high amongadolescents with pelvic pain symptom. Deposits of tissue outside uterine cavity depend on oestrogen.Progestins and oral contraceptives are not successful 1/3 of symptomatic women worldwide. Pathogenesisof endometriosis is not well understood but immune system plays a role in its pathophysiology. Theaetiology of endometriosis remains largely unknown. Here in this review, reader may find a review ofsystematic reviews and meta-analysis published after 2015 on endometriosis.